2007
DOI: 10.1007/s10803-007-0478-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Autism Prevalence: Diagnostic Substitution Revisited

Abstract: There has been little evidence to support the hypothesis that diagnostic substitution may contribute to increases in the administrative prevalence of autism. We examined trends in assignment of special education codes to British Columbia (BC) school children who had an autism code in at least 1 year between 1996 and 2004, inclusive. The proportion of children with an autism code increased from 12.3/10,000 in 1996 to 43.1/10,000 in 2004; 51.9% of this increase was attributable to children switching from another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 22 publications
6
69
1
6
Order By: Relevance
“…Using education records, Shattuck (2006) found a rising number of children with an ASD exceptionality correlated temporally with a declining number with an Intellectual Disability (ID) or Learning Disability (LD) exceptionality. Coo et al (2008) studied education records of individual children longitudinally and reported that switching to an autism exceptionality from another classification accounted for 51.9 % of this study's increase in autism prevalence. However, Newschaffer et al (2005) found an increase in autism classifications among birth cohorts between 1987 and 1992, with no subsequent decrease in ID or Speech/Language impairment.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using education records, Shattuck (2006) found a rising number of children with an ASD exceptionality correlated temporally with a declining number with an Intellectual Disability (ID) or Learning Disability (LD) exceptionality. Coo et al (2008) studied education records of individual children longitudinally and reported that switching to an autism exceptionality from another classification accounted for 51.9 % of this study's increase in autism prevalence. However, Newschaffer et al (2005) found an increase in autism classifications among birth cohorts between 1987 and 1992, with no subsequent decrease in ID or Speech/Language impairment.…”
Section: Introductionmentioning
confidence: 89%
“…Individuals currently recognized as having an ASD might formerly have received services under a classification of another related condition, such as intellectual disability, speech/ language impairment, or learning disabilities. Most studies supporting (Shattuck 2006;Croen et al 2002;Coo et al 2008) and refuting this theory (Gurney et al 2003;Newschaffer et al 2005) utilize aggregate special education data. Using education records, Shattuck (2006) found a rising number of children with an ASD exceptionality correlated temporally with a declining number with an Intellectual Disability (ID) or Learning Disability (LD) exceptionality.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ASD appears to have increased substantially over several decades and may be as high as 1 in 150 children [6][7][8]. In families with one child with ASD, the prevalence rate for their sibling is 20-50-times higher than that of the population base rate [9].…”
Section: Rehabilitation Issues In Autism Spectrum Disordersmentioning
confidence: 99%
“…In families with one child with ASD, the prevalence rate for their sibling is 20-50-times higher than that of the population base rate [9]. Whether the reported increase is a result of actual prevalence or a combination of factors such as broadening diagnostic criteria, increased awareness and changes in relevant policy is currently unknown [6][7][8]. The precise aetiology of ASD is similarly unknown; however, it is likely multifactorial, with many agents, genetic and environmental, possibly effecting the presentation of symptoms [9][10][11].…”
Section: Rehabilitation Issues In Autism Spectrum Disordersmentioning
confidence: 99%
“…Part of the increased prevalence can be attributed to increased clinician awareness of the disorder and to diagnostic substitution [11][12][13][14] but the increase may also result from environmental changes, including a growing variety of pollutants that are ubiquitous in our environment [15,16].…”
mentioning
confidence: 99%